2014
DOI: 10.1186/2193-1801-3-521
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total lipids and fatty acids from liver, heart and abdominal muscle of scalloped (Sphyrna lewini) and smooth (Sphyrna zygaena) hammerhead sharks

Abstract: Liver, heart and abdominal muscle samples from scalloped (Sphyrna lewini) and smooth (Sphyrna zygaena) hammerhead sharks were analysed to characterise their lipid and fatty acid profiles. Samples were compared both between and within species, but there were no significant differences in total lipids for either comparison, although much greater total amounts were found in the liver samples. Within the individual fatty acids, the only significant differences were greater amounts of 22:6n-3, total n-3 polyunsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(53 reference statements)
0
7
2
Order By: Relevance
“…The reference list of the resulting articles was then searched for additional citations containing appropriate FA profiles. Only those derived from muscle tissue were used in the analysis, as they most closely resemble prey FA profiles (Beckmann, Mitchell, Stone, & Huveneers, ; McMeans et al., ; Pethybridge et al., ), have less intra‐ and inter‐individual variability (Davidson et al., ; Pethybridge, Daley, Virtue, Butler, et al., ; Pethybridge, Daley, Virtue, & Nichols, ) and are dominated by essential polyunsaturated FA (PUFAs), (Davidson et al., ; Pethybridge, Daley, Virtue, Butler, et al., ; Pethybridge, Daley, Virtue, & Nichols, ) which are the predominant FAs used to examine the influencing biotic and abiotic factors (Colombo et al., ; Gladyshev et al., ; Vasconi et al., ). Furthermore, liver was not assessed within this study as the FA profiles are likely heavily influenced by physiological factors (including migration, buoyancy, diet, pregnancy, energy availability [Ballantyne, ; Pethybridge, Daley, Virtue, Butler, et al., ; Pethybridge, Daley, Virtue, & Nichols, ]), potentially confounding the influence of abiotic and biotic drivers of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The reference list of the resulting articles was then searched for additional citations containing appropriate FA profiles. Only those derived from muscle tissue were used in the analysis, as they most closely resemble prey FA profiles (Beckmann, Mitchell, Stone, & Huveneers, ; McMeans et al., ; Pethybridge et al., ), have less intra‐ and inter‐individual variability (Davidson et al., ; Pethybridge, Daley, Virtue, Butler, et al., ; Pethybridge, Daley, Virtue, & Nichols, ) and are dominated by essential polyunsaturated FA (PUFAs), (Davidson et al., ; Pethybridge, Daley, Virtue, Butler, et al., ; Pethybridge, Daley, Virtue, & Nichols, ) which are the predominant FAs used to examine the influencing biotic and abiotic factors (Colombo et al., ; Gladyshev et al., ; Vasconi et al., ). Furthermore, liver was not assessed within this study as the FA profiles are likely heavily influenced by physiological factors (including migration, buoyancy, diet, pregnancy, energy availability [Ballantyne, ; Pethybridge, Daley, Virtue, Butler, et al., ; Pethybridge, Daley, Virtue, & Nichols, ]), potentially confounding the influence of abiotic and biotic drivers of interest.…”
Section: Methodsmentioning
confidence: 99%
“…This is evidenced by recent isotopic studies on white sharks, Carcharodon carcharias, whereby muscle and subdermal tissue had the same 15 N isotopic signatures, but divergent 13 C signatures, which was attributed to differing tissue-specific incorporation rates (Carlisle et al, 2012;Kim et al, 2012;JaimeRivera et al, 2013). How these tissue-specific physiological and biochemical differences manifest in FA profiles remains poorly studied, with most elasmobranch work to date focused on the FA differences between skeletal muscle and the lipid-rich liver (e.g., Schaufler et al, 2005;Pethybridge et al, 2011;Beckmann et al, 2013), myocardial tissue (Davidson et al, 2011(Davidson et al, , 2014, and blood plasma (Ballantyne et al, 1993;McMeans et al, 2012). However, Every et al (2016) recently showed differences in FA profiles between muscle tissue and fin clips (a mixed-tissue sample, including cartilage, connective tissue, muscle, vascularization and an outer dermal layer with denticles).…”
Section: Introductionmentioning
confidence: 99%
“…This becomes particularly challenging when there are scarce opportunities for sampling (e.g., for highly mobile, rare, or cryptic species) and when working in remote and hostile field locations (e.g., hot and humid tropics, and offshore sampling sites). Furthermore, despite the growing utilization of non-lethal biopsies, many FA studies use samples taken from deceased elasmobranch carcasses obtained from fisheries bycatch (Pethybridge et al, 2011), beach strandings , and shark-control measures (Davidson et al, 2011(Davidson et al, , 2014Pethybridge et al, 2014). Given the variable condition of these carcasses, which may have spent multiple days at ambient temperature, there is the high potential for lipid and FA degradation within samples collected via these means.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different elasmobranch tissues, such as muscle, liver, reb blood cells, blood plasma, ect., have distinct physiologies, metabolic roles (Speers‐Roesch & Treberg, 2010), lipid classes, and FA profiles (Davidson et al ., 2014; Meyer et al ., 2017; Pethybridge et al ., 2011), it does not infer that individual tissues cannot be used to explore the impacts of tourism on shark diet and nutritional condition. Selecting the appropriate tissue is challenging, critical, and frequently discussed among trophic ecologists (Budge et al ., 2006; Munroe et al ., 2018; Pethybridge et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%